A174: JIA‐Associated SNPs From Non‐Coding Regions Are Located Within or Adjacent to Functional Genomic Elements of Human Neutrophils. Issue 11 (March 2014) - Jarvis, James N.; Jiang, Kaiyu; Liu, Tao; Buck, Michael; Carrier, Bradley; Chen, Yanmin
Abstract : Background/Purpose: The recent completion of a large genome‐wide associate study (GWAS) for juvenile idiopathic arthritis (JIA) revealed multiple genomic regions conferring disease risk (Nature Genet 2013). However, as is typical of most GWAS, the majority of disease‐associated SNPs occurred in noncoding regions of the genome, either in intergenic regions or introns. This finding suggests, therefore, that disease risk for JIA resides in the control and coordination of transcription, rather than in malfunction of genetically‐altered proteins. This study was undertaken, therefore, to identify functional elements that might be associated with the identified, disease‐associated SNPs in polyarticular, RF‐negative JIA. Methods: We first generated a genome wide map of histone marks associated with enhancer elements in healthy adult neutrophils. Using chromatin immunoprecipitation/sequencing (ChIPseq) approaches, we mapped the histone marks associated with poised (H3K4me1+/H3K27ac−) or active (H3K4me1+/H3K27ac+) enhancers to the GRCh37/hg19 genome assembly. In addition, we performed paired‐end RNA sequencing on neutrophils from 5 children with newly diagnosed, untreated polyarticular, RF‐negative JIA and mapped reads to the same human genome assembly. These results were used to interrogate ENCODE and Roadmap Epigenomics data; we used the UCSC Genome browser to interrogate the 22 polyarticular JIA associated SNPs from non‐coding regions genome identified by Hicks et al (Nature Genet 2013) as conferring risk for polyarticular JIA. Results: Using the approach above, we ascertained that there are functional elements in neutrophil genomes in or adjacent to 13 of the 22 SNP regions identified by Hicks et al. Enhancer elements were the most frequently identified functional elements in this study, with 9 potentially active (H3K4me1+/H3K27ac+) and 3 additional potentially poised enhancers identified. We also identified 4 non‐coding transcripts within the SNP regions. Four of these regions (e.g., both of the SNPs around C5orf56‐IRF1) contained both non‐coding RNA transcripts and enhancer elements. It was also interesting to note abundant intronic transcription in other genes relevant to inflammation/immunity but not otherwise known to confer genetic risk e.g., CD36. Conclusion: Regions of known genetic risk for polyarticular JIA are rich with functional elements that are believed to regulate and coordinate transcription in human neutrophils. These data provide a new framework from which to understand genetic risk and disease pathogenesis in JIA, and suggest that transcriptional regulation and coordination may be a process that is fundamentally perturbed in this disease.